Structural design and optimization of double-cross shape broadband absorption metamaterial based on CB-ABS - Chen, Mengzhou; Wang, Liuying; Liu, Gu; Ge, Chaoqun; Wang, Long; Xu, Kejun; Wang, Weichao (Frontiers in Materials, 2022)
This work presents a novel broadband double-layer UK-Flag shape metamaterial structure based on the Carbon Black-Acrylonitrile-Butadiene-Styrene (CB-ABS) composite material. The optimal metamaterial structure with the thickness of 7 mm shows a broadband absorption characteristic in the frequency range of 5.1- 40 GHz. Additionally, the low volume filling fraction of proposed metamaterial structure will be helpful to achieve lightweight broadband absorption performance. Meanwhile, the metamaterial structure also can display a wide-angle absorption performance from 0° to 55° for TE mode and 0° to 75° for TM mode. Moreover, this research provides an effective and promising way of lightweight broadband and wide-angle microwave strong absorption metamaterial for practical application in the future.